2017
DOI: 10.1172/jci88888
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac nuclear receptors: architects of mitochondrial structure and function

Abstract: The adult mammalian heart has immense energy demands in order to support its role as a constantly active pump. Indeed, the human heart generates and utilizes kilogram quantities of ATP each day. The vast majority of ATP produced in the cardiac myocyte is generated via oxidative phosphorylation (OXPHOS) within a very-high-capacity mitochondrial system. The heart must continually adapt to changing physiologic conditions that influence workload, as well as alterations in oxygen and energy substrate availability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 128 publications
(138 reference statements)
1
54
0
Order By: Relevance
“…Detailed cardiac and renal analysis of diabetic animal models has revealed that SGLT2i affect mitochondrial morphology and density . Mitochondrial content and respiratory capacity are also significantly reduced in HF, which is tied to diminished expression of the transcription factor PGCā€1Ī± . To determine whether the favourable effects of EMPA on cardiac remodelling were associated with similar recovery of mitochondrial biogenesis, mitochondrial content was quantified by normalizing mtDNA to nDNA.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed cardiac and renal analysis of diabetic animal models has revealed that SGLT2i affect mitochondrial morphology and density . Mitochondrial content and respiratory capacity are also significantly reduced in HF, which is tied to diminished expression of the transcription factor PGCā€1Ī± . To determine whether the favourable effects of EMPA on cardiac remodelling were associated with similar recovery of mitochondrial biogenesis, mitochondrial content was quantified by normalizing mtDNA to nDNA.…”
Section: Resultsmentioning
confidence: 99%
“…The contributions of the nuclear receptor superfamily to regulating cardiac physiology through ligand-dependent transcriptional regulation have increasingly been recognized (17,27). Although cardiomyocyte nuclear receptors are best known for regulating metabolism, they also participate in numerous other cellular functions (42), including the transcriptional regulation of sarcomeric and Ca 2Ļ© -handling genes (8). The retinoic acid-related orphan receptor (ROR) subfamily of nuclear receptors consists of RORā£, RORā¤, and RORā„ (NR1F1-NR1F 3) (6,19).…”
Section: Introductionmentioning
confidence: 99%
“…Over the first week of life, the heart switches to metabolism of fat via the fatty acid oxidation (FAO)Ā pathway 40. There is a complex signalling mechanism that orchestrates these changes 41. In utero hypoxia-inducible factors (HIF-1Ī±) promote the glucose transporter GLUT-1 and favour glucose metabolism.…”
Section: Cardiac Function and Haemodynamics After Birthmentioning
confidence: 99%